Bone marrow edema-like lesions (BMELs) are associated with higher T(1ρ) and T(2) values of cartilage in anterior cruciate ligament (ACL)-reconstructed knees: a longitudinal study - Gong, Jingshan (Quant Imaging Med Surg, 2016)
BACKGROUND: To evaluate the longitudinal changes of bone marrow edema-like lesions (BMELs) in patients after anterior cruciate ligament (ACL) reconstruction and to investigate the effect of BMELs on cartilage matrix composition changes measured using MR T(1ρ) and T(2) mapping. METHODS: Patients with acute ACL tear were enrolled in a prospective study. MR imaging was performed at baseline (before surgeries) and at 6-month, 1-year and 2-year after ACL reconstruction. MR imaging included sagittal high-resolution, 3D fast spin-echo (CUBE) sequences for BMEL evaluation, and 3D T(1ρ) mapping and T(2) mapping for cartilage assessment. BMELs were assessed using whole-organ magnetic resonance imaging score (WORMS), and the volume of BMELs was measured by a semi-automatic method. Generalized estimating equation (GEE) was used to explore association between BMELs at baseline and cartilage changes during follow-up. RESULTS: Fifty four patients were included in the present study and 39 patients had completed 2-year follow-up. BMELs were noted in 42 injured knees (77.8%) with 105 lesions and in 7 contralateral knees (13.0%) with 9 lesions (χ(2)=45.763, P<0.001) at the baseline. The WORMS and volume of BMELs of the injured knees were 2.36±0.65 and 386.98±382.54 mm(3) (r=0.681, P<0.001), respectively. 87 BMELs were found at baseline in 34 patients (87.2%) of the 39 patients who had completed 2 years follow-up. During the follow-up, 18 (20.7%), 12 (13.8%), and 5 (5.7%) baseline lesions were still seen at 6-month, 1-year and 2-year, respectively. The changes of BMELs prevalence regarding bone compartments over time points were statistically significant (χ(2)=163.660, P<0.001). Except T(2) value at 6 months, T(1ρ) and T(2) values of cartilage overlying baseline BMELs in the injured knees were higher than that of anatomically matched cartilage in the contralateral knees at baseline and each follow-up time-point. In the injured knees, GEE analysis showed that baseline BMELs were significantly associated with higher T(1ρ) and T(2) values of cartilage after adjustment of age, gender, body mass index (BMI), effusion and meniscus tear. The association between BMELs and Knee Injury and Osteoarthritis Outcome Scores (KOOS) scores was not statistically significant. CONCLUSIONS: BMEL is a common finding in patients with acute ACL injury and resolves rapidly over time after ACL reconstruction. It is often associated with increased T(1ρ) and T(2) values of cartilage. BMEL at baseline is an independent predictor for faster cartilage degeneration during follow-up.